Correlation between D-dimer and size of middle cerebral artery infarction and its relation to functional outcome - Ramy Taha Alloush; Mohamed Hamdy Ibrahim; Shahinaz Mohamed Helmy; Aya Ebrahim Marwan; Mona Ali Eissa; Adel T. Alloush; Mohamed Khaled Elewa (The Egyptian Journal of Neurology, Psychiatry and Neurosurgery)
Abstract Background The correlation between D-dimer and middle cerebral artery (MCA) acute infarction size, was not fully studied before up to our knowledge, despite it could have a predictive value for patients’ functional outcomes and might influence decision making. Methods To examine the relationship between the severity of ischemic MCA infarction and plasma D-dimer level. Thirty MCA acute ischemic stroke (AIS) patients who met the inclusion and exclusion criteria were included in this longitudinal investigation. A particle-enhanced immunoturbidimetric technique was utilized to assess the plasma D-dimer concentration for each patient at the time of admission. Furthermore, data from neuroimaging, clinical, laboratory, and demographic sources were examined. Additionally, the modified Rankin Scale (mRS) score was used to evaluate the predictive usefulness of plasma D-dimer on a patient's functional outcome after three months. Results There was a statistically significant positive correlation between D-dimer levels on admission and the initial infarction size in diffusion weight imaging (DWI) MRI. There was a direct statistically significant positive correlation between the D-dimer and the mRS scores of the patients, and the best cut-off limit of D-dimer levels done to patients early after admission (in the first 24 h) in predicting poor outcome was 650 ng/ml, which achieves 85.71% sensitivity and 87.5% specificity. Conclusion D-dimer evaluation might serve as a useful adjunct to neuroimaging for early ischemic stroke detection and evaluation.